Radiofrequency diathermy for uniform heating of mouse tumours. - Joiner, M. C. (Nature Publishing Group, 1982)
A system has been developed for uniformly heating mouse tumours by using a combination of 27.12 MHz radiofrequency electric fields (RF) and immersion in heated liquid. Continuous tumour thermometry with implanted thermocouples is necessary in order to modulate the RF power to maintain a constant temperature over 1 h. Tumours implanted intramuscularly in the hind limbs of mice were heated between a pair of 1.9 cm diameter parallel copper plates. The optimum temperature profile was achieved if the RF heating was combined with immersion of the limb in circulating saline, preheated to the desired temperature. This method of electrical coupling between the plates and tissues has been shown to be significantly better than using ECG jelly or unheated liquid, and it is better than simple immersion in heated liquid without RF. A temperature monitoring system has been developed, using fine thermocouples implanted into the tumour, to regulate the applied RF power. Each complete thermocouple probe is less than 0.5mm in diameter and consists of 6 separate monitoring junctions spaced at 1.5mm intervals along its length. Using this monitoring system the temperature within tumours has been maintained constant (+/- 0.1 degrees C) for a period of 1 h.